Comparación de lima protaper gold y mtwo en la modificación de conductos curvos según el método de Schneider, 2022 - Flores Bautista, Genesis Guadalupe (2023)
The purpose of this research work was the comparison of the Protaper Gold and Mtwo files in the modification of curved canals according to the Schneider method, 2022. The research was of a quantitative type, of an experimental design, of the quasi-experimental type. The study population was the mesiobuccal canals of 40 permanent mandibular first molars, of which 20-mesiobuccal canals were used for each rotary system. The data collection sheet for the angle of curvature according to the Schneider method was used as an instrument. The most relevant results were: Before instrumentation, the most frequent degree of curvature of the mesiobuccal canals selected for the Protaper Gold file was 30° and 32° with 15% each. Before instrumentation, the canals presented severe angulation at 100% and at the group selected for instrumentation with the MTWO file was 24°, 25° and 30° with 15% each, presented a severe angulation of 55% and a moderate angulation of 45%. After instrumentation with the MTWO file, the most frequent degree of curvature was 23° with 15%, and they presented severe angulation of 55% and moderate angulation of 45%. The mean angle of the teeth to work with Protaper Gold was 32.10° and decreased 1.5° with the instrumentation, reaching 30.60°. The mean of the angle of the group of teeth to work with Mtwo was 25.55° and decreased with the instrumentation 1.8°, reaching 23.75°. There is no significant difference in the Protaper Gold group before and after instrumentation (p=0.289). There is a significant difference in the MTWO group before and after instrumentation (p=0.000).